The sociology of contraband: Examining the correlates of illicit drugs, cellphones, and weapons in U.S. prisons - Peterson, Bryce E. (The prison journal, 2024)
Contraband negatively affects the safety and security of correctional institutions. Extant research has relied on descriptive analyses or limited measures of contraband. Drawing upon established theories of institutional misbehavior—the deprivation model, importation model, and management perspective–the study examines facility-level and correctional population characteristic correlates of contraband in 301 prisons across six U.S. states. Findings confirm the relevance of individually examining risk factors by type of contraband, including drugs, cellphones, weapons, and total contraband. Lower security prisons, prisons providing substance use treatment, and those employing more women staff had fewer contraband drugs, weapons, and cellphones. Providing outside work opportunities and work-release programs also reduced contraband weapons.